The Influence of Service Quality and Digital Payment on Purchasing Decisions at PT. Plangkaraya Semi Mart - Sirwindy; Petrus Loo (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
The retail business in the city of Medan is growing day by day, this makes retail business managers have to work harder to stay in the competition. This study aims to analyze the effect of service quality, digital payments influence on purchasing decisions at PT. Plangkaraya Semi Mart. This research is a descriptive research with a quantitative approach. The sample of 104 respondents selected through non-probability sampling were consumers at PT. Plangkaraya Semi Mart. Data collected through questionnaires collected data analyzed by multiple linear regression. The results showed that the quality of service and digital payments had a partial or simultaneous effect on purchasing decisions at PT.Plangkaraya Semi Mart and Service Quality are the most dominant variables affecting purchasing decisions at PT. Plangkaraya Semi Mart. In this study proves that good service quality is able to direct and ultimately will encourage the formation of purchasing decisions. With the existence of digital payments, and the increasing use of digital payment applications indicate that consumers have been fulfilled and satisfied with their needs.